Women Street Artists in the Southern and Eastern Districts of Madrid: A Netnographic Analysis - Pérez Asperilla, Estíbaliz (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
This study focuses on the southern and eastern districts of Madrid, based on the neighbourhood movement that began in 2018, which demanded, among other issues, the recovery and regeneration of degraded urban spaces. A netnographic analysis of Instagram publications identifies artistic interventions by women street artists in these districts, defines the themes and messages they convey, and demonstrates the links and relationships established. Finally, the role of Instagram is analyzed, not only as an art gallery but also as a dissemination tool, enabling the visibility of the work of the women urban artists under study.